ECONOMIC ANALYSIS OF PATCHOULI FARMING IN KLUET TIMUR SUB-SUB-DISTRICT, ACEH SELATAN - Sri Harita; Adhiana Adhiana; Naz'aina Naz'aina (LPPM Universitas Malikussaleh - Indonesia, 2024)
Patchouli plants are one of the potential commodities cultivated in Kluet Timur Sub-District. To be able to grow and produce well, patchouli plants require feasibility analysis and utilization of production factors Which is optimal. Study This aims For analyzing (1) Factors that influence the production of patchouli plants in Kluet Timur Sub-Sub-District, (2) The level of economic feasibility of patchouli farming in Kluet Timur Sub-District, Aceh Selatan. This research was carried out in Kluet Timur Sub-Sub-District, Aceh Selatan. The research was carried out using the Census method, with respondents deliberately selected using the criteria of independent farmers who have patchouli gardens. From the research results, the results showed that factors that have a significant influence on the production of patchouli farming in Kluet Timur Sub-Sub-District are land area, chemical fertilizer and labor. Meanwhile, seed and pesticide factors do not have a significant effect on patchouli farming production in Kluet Timur Sub-District. The value of the R/C Ratio is 2.64 (R/C Ratio > 1), the B/C Ratio is 1.64 (B/C Ratio > 1), which means that patchouli farming is feasible. The production BEP is 13.26, the price BEP is 208,358, the production value of the patchouli farming business obtained is more than the BEP value. So patchouli farming in Kluet Timur Sub-District is profitable. Keywords: Farming, Production Factors, Feasibility, Patchouli Farming.